2018
DOI: 10.18388/abp.2018_2658
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury by cyclosporine A is aggravated in heme oxygenase-1 deficient mice and involves regulation of microRNAs

Abstract: Cyclosporine A (CsA), a widely used immunosuppressive drug, exerts nephrotoxic activities, as demonstrated by increased tubulointerstitial fibrosis, inflammation and podocyte damage. Recently, a number of microRNAs expressed in the kidney have been reported to be elevated during renal damage. Our aim was to investigate the effect of CsA on selected microRNAs in the mouse kidney after CsA treatment. Moreover, as heme oxygenase-1 (HO-1, encoded by the Hmox1 gene) was shown to play a protective role during kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The mechanism might be related to HO-1 and downstream NF-E2related factor 2 translocation to the nucleus and its effect on gene expression [58][59][60][61] . A study by Loboda et al 62 showed that cyclosporine A decreased the expression of miR-200b significantly in Ho-1 (−/−) proximal tubular epithelial cells. By detecting the level of miR-200b in BMMSC cells and exosomes stimulated by TNF-α and HO-1 modification, we found that the expression level of miR-200b in BMMSCs with both HO-1 modification and TNF-α stimulation was significantly higher than that after single factor stimulation and in unstimulated BMMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism might be related to HO-1 and downstream NF-E2related factor 2 translocation to the nucleus and its effect on gene expression [58][59][60][61] . A study by Loboda et al 62 showed that cyclosporine A decreased the expression of miR-200b significantly in Ho-1 (−/−) proximal tubular epithelial cells. By detecting the level of miR-200b in BMMSC cells and exosomes stimulated by TNF-α and HO-1 modification, we found that the expression level of miR-200b in BMMSCs with both HO-1 modification and TNF-α stimulation was significantly higher than that after single factor stimulation and in unstimulated BMMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial Permeability Transition Pore Inhibitors Mitochondrial membrane depolarization, which is induced by the opening of the mitochondrial permeability transition pore (mPTP) in the mitochondrial membrane, can significantly interrupt ETC and then lead to decreased energy production, increased ROS production, and cell death. Cyclosporine-A (CsA) is a well-known immunosuppressant interacting with cyclophilin A and is clinically used in the treatment of graft rejection and autoimmune diseases, including kidney disease [179]. In addition, CsA is also known as an mPTP inhibitor, which can bind to cyclophilin D of the mPTP and inhibit mPTP opening [180].…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…This fraction of "free or loosely" bound heme also termed "labile" is biologically active and high levels of labile heme are considered to be cytotoxic and to aggravate inflammation and tissue injury (9,10). In support of this notion are the findings that the deficiency of the heme-degrading enzyme heme oxygenase-1 aggravates renal injury in different models of nephrotoxicity (11,12).…”
Section: Introductionmentioning
confidence: 99%